Critical Factors in Developing Asnaf Faqir’s Career Path According to Al-Ghazali - Akbar, Abdul Azim; P. Rameli, Mohd Faizal; Mohd Nor, Ahmad Rosli; Johari, Muhd Khudri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
Asnaf Faqir refers to a group of indigent people who have no source of income, possess neither property or material of their own, and they earn less than 50 percent of their own and their dependents’ basic necessities in life. This study was conducted to identify the indicators that can be used to steadily empower destitute people based on Imam Al-Ghazali’s thoughts and views. The subsequent findings produced a basic framework for the formation of Asnaf Faqir’s career path, based on the concept of spirituality. This qualitative study used library methods for the data collection. The data for this study were collected through various documents and manuscripts, including the Holy Quran, Books of Hadith, Al-Ghazali’s works, journal articles, and others. The data for this study were analyzed deductively and inductively to extract basic spiritual principles related to career paths, as suggested by Al-Ghazali. This study shows that the elements of al-Ruh, al-Insan, al-‘Aql, al-Qalb and al-Jasad of humans are important in shaping the career path of Asnaf Faqir. These five elements were found to be critical factors in fulfilling the planning, exploration, gathering of information, and determination of the career path of Asnaf Faqir as entrepreneurs or skilled workers.